Predictive factors for adverse outcomes in pediatric patients undergoing low‐risk skin and soft tissue surgery: A database analysis of 6730 patients. Issue 1 (30th December 2018) - Cheon, Eric C.; Longhini, Anthony B.; Lee, Joseph; Hansen, Jennifer; Jagannathan, Narasimhan; De Oliveira, Gildasio S.; Suresh, Santhanam
Summary: Background: There is a paucity of data regarding risk stratification of pediatric patients presenting for low‐risk skin and soft tissue surgery. Aims: We sought to determine the incidence and independent predictors of postoperative complications and unplanned 30‐day readmission in a cohort of children undergoing low‐risk skin and soft tissue surgery. Methods: The study included pediatric patients who underwent minor procedures of the skin and soft tissue at continuously enrolled American College of Surgeons National Surgical Quality Improvement Program Pediatric hospitals over a two‐year period. The primary outcome was a 30‐day postoperative complication composite. The secondary outcome was unplanned 30‐day readmission. Results: The final analysis included 6, 730 patients. There were a total of 170 postoperative complications among 152 patients (2.23%) with the majority of complications being either wound‐related or postoperative mechanical ventilation. The independent predictors for an increased risk of postoperative complication were American Society of Anesthesiologists classification ≥3 and nutritional deficiency. There were 41 unplanned readmissions (0.61%). The presence of a postoperative wound complication or a postoperative pulmonary complication during the index hospital stay was an independent risk factor for unplanned 30‐day readmission. Conclusion: Pediatric patients with American Society of Anesthesiologists classification ≥3 and nutritional deficiency undergoing low‐risk surgery are at risk for the development of postoperative complications. Patients who develop wound and postoperative pulmonary complications are at higher risk for unplanned 30‐day readmission. Identification of these higher risk patients may allow the anesthesiologist to implement targeted therapies to minimize the likelihood of occurrence of these complications.